Motivação para a prática de atividade física: uma revisão de literatura - Rodrigues, Giovanna Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Several studies and research indicate that the regular practice of physical activity has numerous health-related benefits. Studies show that the practice of physical activity is one of the most efficient tools for health promotion, and new research emphasizes that people who are physically active live longer than sedentary individuals. Despite all these data, these factors do not seem to be crucial and sufficient to make sedentary individuals practice and maintain a certain consistency with regard to physical activity. This study is a review that aims to analyze and present the reasons why the population performs the regular practice of physical activity. Searches were carried out based on selected articles in which the reasons for the practice of physical activity were highlighted. The searches were carried out in the following databases: Scielo, Google Scholar and Capes. It can be concluded that adolescents are mainly motivated by intrinsic aspects and factors, predominantly by the category of pleasure, status and, finally, personal achievements and competitiveness in the practice of PA. However, in the adult and elderly phase, the most relevant factors change, and aspects of physical conditioning and health, weight loss and aesthetics become more relevant, that is, extrinsic factors in evidence.

Diversos estudos e pesquisas apontam que a prática regular de atividade física apresenta inúmeros benefícios relacionados a saúde. Estudos mostram que a prática de atividade física é uma das ferramentas mais eficientes para a promoção de saúde, além de novas pesquisas ressaltam que pessoas que são ativas fisicamente vivem mais do que indivíduos sedentários. Apesar de todos esses dados, esses fatores não parecem ser cruciais e suficientes para fazer com que indivíduos sedentários pratiquem e se mantenham em uma certa constância no que diz respeito a atividade física. Esse estudo é uma revisão que tem como objetivo analisar e apresentar quais são os motivos pelos quais a população realiza a prática regular de atividade física. Foram realizadas buscas com base em artigos selecionados em que se destacou os motivos para a pratica de atividade física. As buscas foram realizadas nas bases de dados: Scielo, Google Acadêmico e Capes. Pode-se concluir que os adolescentes são motivados principalmente por aspectos e fatores intrínsecos, predominantemente pela categoria prazer, status e por último realizações pessoais e competitividade na prática de AF. Entretanto, na fase adulta e idosa, os fatores mais relevantes se modificam, e aspectos de condicionamento físico e saúde, emagrecimento e estética se tornam mais relevantes, ou seja, fatores extrínsecos em evidência.
Motivation to practice physical activity: a literature review
Keywords: Physical activity; Motivation; Health; Exercícios físicos; Motivação; Saúde; Physical activity; Motivation; Healt